2022
DOI: 10.1038/s41598-022-10709-8
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular polarization-sensitive optical coherence tomography based on polarization mode delay

Abstract: Intravascular polarization-sensitive optical coherence tomography (IV-PSOCT) provides depth-resolved tissue birefringence which can be used to evaluate the mechanical stability of a plaque. In our previous study, we reported a new strategy to construct polarization-sensitive optical coherence tomography in a microscope platform. Here, we demonstrated that this technology can be implemented in an endoscope platform, which has many clinical applications. A conventional intravascular OCT system can be modified fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It has also been reported that OCT has high sensitivity and specificity in detecting lipid-rich plaques, verified by autopsy specimens (90-94% and 90-92%, respectively) (55). Another study demonstrated a significant correlation between FC thickness, lipid core size, and the proportion of lipid content between groups through OCT measurement (56), confirming the high efficiency of OCT. Moreover, OCT cap thickness measurements were associated with the prevalence of plaque rupture (57).…”
Section: Optical Coherence Tomographymentioning
confidence: 68%
“…It has also been reported that OCT has high sensitivity and specificity in detecting lipid-rich plaques, verified by autopsy specimens (90-94% and 90-92%, respectively) (55). Another study demonstrated a significant correlation between FC thickness, lipid core size, and the proportion of lipid content between groups through OCT measurement (56), confirming the high efficiency of OCT. Moreover, OCT cap thickness measurements were associated with the prevalence of plaque rupture (57).…”
Section: Optical Coherence Tomographymentioning
confidence: 68%